2009
DOI: 10.1136/vr.164.18.550
|View full text |Cite
|
Sign up to set email alerts
|

Responses of pigs to a re‐challenge with Actinobacillus pleuropneumoniae after being treated with different antimicrobials following their initial exposure

Abstract: Four groups of six specific pathogen-free (SPF) pigs were inoculated intranasally with Actinobacillus pleuropneumoniae serotype 2 and treated with either enrofloxacin, tetracycline or penicillin at the onset of clinical disease, or left untreated. A fifth group was left uninoculated. The inoculated control and the penicillin-treated groups developed severe disease, but the groups treated with enrofloxacin and tetracycline recovered rapidly. All the inoculated pigs, except those treated with enrofloxacin develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…However, these two pigs did develop moderate levels of serum antibodies to A pleuropneumoniae serotype 2. The protective role of antibodies against A pleuropneumoniae infections has been reported previously (Cruijsen and others 1995, Sjölund and others 2009), and is further supported as the two pigs that did not mount an acute phase response were no more severely affected than the other pigs with respect to clinical signs and lesions at postmortem examination. The mild clinical signs observed in these pigs implies that a strong immune response is correlated with more severe signs of disease in A pleuropneumoniae infections.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…However, these two pigs did develop moderate levels of serum antibodies to A pleuropneumoniae serotype 2. The protective role of antibodies against A pleuropneumoniae infections has been reported previously (Cruijsen and others 1995, Sjölund and others 2009), and is further supported as the two pigs that did not mount an acute phase response were no more severely affected than the other pigs with respect to clinical signs and lesions at postmortem examination. The mild clinical signs observed in these pigs implies that a strong immune response is correlated with more severe signs of disease in A pleuropneumoniae infections.…”
Section: Discussionsupporting
confidence: 81%
“…The clinical signs, leucocyte counts and serological responses of the experimental inoculations with A pleuropneumoniae have previously been described in detail (Sjölund and others 2009). In brief, the clinical scores for the pigs in the enrofloxacin-treated group only differed from the uninoculated control group 20 hours after the first inoculation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, it has been shown that pigs experimentally inoculated with A. pleuropneumoniae serovar 2 and injected with enrofloxacin after onset of clinical sign had evidence of interference with antibody production to A. pleuropneumoniae. 44 In the present study, ceftiofur was used for treatment of clinically affected pigs, and it is possible that the antigenic load in treated pigs was reduced, resulting in a reduced or even absent humoral immune response. A previous report on the evaluation of ELISAs for A. pleuropneumoniae also showed that antibodies against some serovars could not be detected.…”
Section: Discussionmentioning
confidence: 99%
“…Because antimicrobial treatment may interfere with antibody production, 44 seroconversion to A. pleuropneumoniae was verified by additional assays in selected pigs. All samples from a pig collected after inoculation were excluded if there was no indication of seroconversion by all 4 assays utilized in this study and by the confirmatory assay(s).…”
Section: Methodsmentioning
confidence: 99%